Severe Hypoglycemia due to Isolated ACTH Deficiency in Children: A New Case Report and Review of the Literature - Michael Y. Torchinsky; Robert Wineman; George W. Moll (International Journal of Pediatrics)
Isolated ACTH deficiency causes life-threatening severe hypoglycemia. A 7-year-old girl with hypoglycemia due to this rare disorder is described. Our patient had undetectable plasma ACTH repeatedly and cortisol 0 mcg/dl before and after ACTH 1-24 stimulation. There was no evidence of other pituitary hormone deficiency. Glucocorticoid replacement therapy resulted in resolution of all symptoms and normalization of blood glucose. Previously published data on isolated ACTH deficiency in children is summarized. Review of the literature showed that the prevalence of this condition could be underestimated in the neonatal period and in Prader-Willi syndrome. Isolated ACTH deficiency occurs in older children as well as in neonates.